Aplicação de técnicas espectroscópicas em combinação com quimiometria para detecção de adulteração em noz-moscada em pó (Myristica fragrans) e canela em pó (Cinnamomum) - Scherner, Marcia (2022)
The use of spices and condiments has followed history since the development of civilizations, being used on a large scale throughout the world for various purposes. According to Food Fraud Requirements Analysis, spices are on the list of foods most susceptible to food fraud. This procedure can occur in several stages of the chain of production, processing, distribution, and commercialization until reaching the consumer, and these products are commonly sold in bulk, without specific labeling, in fairs and natural products stores. Within this food group, cinnamon (Cinnamomum) and nutmeg (Myristica fragrans) are spices that stand out both for culinary use and for cosmetology, as well as being used in folk medicine. Due to the high cost of these spices and appreciation in the international market, these products are constantly subject to adulteration. This practice is even more evident when these products are sold in powder form. Among the products commonly used for adulteration in powdered spices, starches such as cassava starch and corn starch stand out due to their wide availability and low cost, being an option of easy access and inert in terms of flavor, color and aroma. The techniques used to prove fraud are generally more expensive, require analysis time and generate waste, besides destroying the samples, as in the case of chromatographic techniques. Therefore, to evaluate adulterations in these foods, the development of a suitable tool could be achieved through spectroscopy, since it allows for signal measurements without the need for sample preparation (or with minimal preparation), low or free of residues, allowing for sample screening and favoring a more efficient inspection. Thus, this study aimed to evaluate samples of cinnamon and nutmeg through the Fourier-transform mid-infrared spectroscopy and principal component analysis to evaluate the similarity between samples considered as references (pure) and the intentionally adulterated (mixtures), comparing them to samples acquired in the commerce from different regions of Brazil. The results indicated that for both cinnamon and nutmeg samples, the addition of cassava starch and corn starch causes the samples to distance themselves from the reference samples and approach the commercial ones, suggesting the possibility that many commercial samples may be undergoing tampering.